Cooperation and Information Sharing Increase Supply Chain Performance Broiler Egg Traders in Regency of Pandeglang Banten - Moh. Mukhsin (International Business and Accounting Research Journal, 2021)
This study aimed to analyze the cooperation and sharing of information to improve supply chain performance. This research examine the influence cooperation the performance of the supply chain, the impact of information sharing on the performance of the supply chain. Object of this research is Broiler egg traders in Regency of Pandeglang Banten. This study uses a quantitative method using descriptive research and causal research. Data from all three variables was analyzed using the program Structural Equation Model (SEM) in the Software Smart PLS 3.0. m3 version. The data will be used in this research is primary data, by sending questionnaires to 100 respondents Broiler eggs. Based on the results of data analysis can be concluded that the influence of cooperation and information sharing relationships influence a positive and significant influence on supply chain performance.